Food Security Analysis of Smallscale Fishermen in Karanggongso, Trenggalek Regency - Candra Adi Intyas; Agus Tjahjono (Faculty of Fisheries and Marine Science, Brawijaya University, 2019)
Sea resources that open access are causing competitive competition among fishermen. This mainly affects 87.5% of small-scale fishermen in Indonesia who are commonly in poverty. The problems faced are the marketing and production institutions that have not been optimal also the mindset of fishermen who are still subsistence. One way that small-scale fishermen try to increase their income is processing fresh fish to become smoked fish (traditional methode). The purpose of this study was to analyze the level of food security of small-scale fishermen household who also do smoked fish processing activities (NKPA) compared to small-scale fishermen household who did not undertake smoked fish processing (NKNPA). The sampling method uses multi stage cluster sampling. Data analysis used an analysis of food security using the Desirable Dietary Pattern. From the results of the study on the quantity aspect, overall AKE and AKP values in NKPA were 100.71% (good category) and 119.35% (the conditions were very food-resistant) while the NKNPA were 82.58% (moderate category) and 101.50 % (the conditions were very food-resistant). In terms of quality, the calculation of Desirable Dietary Pattern consumption from NKPA had a score of 88.49 and NKNPA of 71.77 which means that the conditions are quite ideal.